Synthesis of Composite Adsorbent from Calcium Carbonate and Cocos Nucifera Carbon Powder Crosslinked with Biopolymer Matrix - Kamaruddin M.A.; Bakri M.M.A.; Norashiddin F.A.; Zawawi M.H.; Zainol M.R.R.A. (Institute of Physics Publishing, 2023)
Biocompatibility; Biomolecules; Calcium carbonate; Carbon; Crosslinking; Pollution; Sintering; Social aspects; Adsorption capacities; Composite adsorbents; Downstream process; Hydrophobic and hydrophilic; Industrial wastewaters; Precipitation methods; Recycling of wastes; Separation and purification; Precipitation (chemical)